Multi-Loop Model of Alzheimer Disease: An Integrated Perspective on the Wnt/GSK3β, α-Synuclein, and Type 3 Diabetes Hypotheses - Norwitz, Nicholas G.; Mota, Adrian Soto; Norwitz, Sam G.; Clarke, Kieran (Frontiers in Aging Neuroscience, 2019)
As the prevalence of Alzheimer disease continues to rise unabated, new models have been put forth to improve our understanding of this devastating condition. Although individual models may have their merits, integrated models may prove more valuable. Indeed, the reliable failures of monotherapies for Alzheimer disease, and the ensuing surrender of major drug companies, suggests that an integrated perspective may be necessary if we are to invent multifaceted treatments that could ultimately prove more successful. In this review, we discuss the Wnt/GSK3B, a-synuclein, and type 3 diabetes hypotheses of Alzheimer disease and their deep interconnection in order to foster the integrative thinking that may be required to reach a solution for the coming neurological epidemic.